(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study explores the effectiveness of the court lesson method as an innovative pedagogical approach to teaching rational equations in mathematics education. Traditional teaching methodologies often fail to foster critical thinking, active participation, and problem-solving skills, necessitating alternative instructional strategies. While previous research has demonstrated the benefits of interactive learning, limited studies have investigated the role of role-based, debate-driven instruction in enhancing mathematical comprehension. This study addresses this gap by implementing court lesson sessions in a controlled classroom setting, where students assume roles such as judges, prosecutors, and witnesses to analyze and debate mathematical problems. A qualitative methodology was employed, utilizing classroom observations, structured interviews, and student reflections to assess engagement, reasoning abilities, and conceptual retention. The findings indicate that students who participated in the court lesson method exhibited higher motivation, improved mathematical argumentation, and reduced math anxiety, supporting the constructivist learning theory. Additionally, results suggest that this method fosters a more inclusive and interactive learning environment. However, challenges remain regarding scalability, teacher training, and adaptation to other mathematical disciplines. Future research should focus on longitudinal studies, technological integration, and broader implementation strategies to enhance the long-term impact and applicability of this approach in mathematics education.